Pendidikan Tauhid dari Kisah Nabi Ibrahim kepada Keluarga (Kajian Tafsir Q.S Ash-Saffat Ayat 100-110) - Dea Amelia Putri; Ikin Asikin; Dinar Nur Inten (Bandung Conference Series: Islamic Education, 2024)
Abstract. Along with the development of the times, many of the teenagers experience increasing moral decadence such as brawls, free sex, drugs that occur among teenagers. This fact is partly due to the lack of attention and affection of parents towards their children. This has a negative impact on the growth and development of their children. Tawhid is the main and first part that must be planted completely and integrally in humans, because it is from the concept of tawhid that this research aims to (1) To find out the opinions of the mufasir on the content of surah Ash-Shaffat 100-110. (2) To find out the values of education in the family. (3) To determine the essence of tawhid education in the family contained in surah Ash-Shaffat 100-110. This research uses a qualitative approach with descriptive methods sourced from literature (library research). considering all the data that is a reference in this thesis comes from written materials, both in the form of books, books and other reading media that are representative and relevant to the object of discussion. The results of this study indicate the essence contained in surah Ash-shaffat verses 100-110. (1) The strongest education in the form of faith (2) Obeying parents is proof of obedience to Allah (3) Patient attitude in the test. Educational values of surah Ash-Shaffat verses 100-110 (1) faith (2) obedience (3) patience. Abstrak. Seiring dengan perkembangn zaman, banyak diantara kalangan remaja mengalami dekadensi moral yang meningkat seperti tawuran, seks bebas, narkoba yang terjadi di kalangan remaja. Kenyataan tersebut antara lain disebabkan oleh kurangnya perhatian dan kasih sayang orang tua terhadap anak-anaknya. Hal ini membuat dampak negatif bagi pertumbuhan dan perkembangan anak-anak mereka. Tauhid merupakan bagian utama dan pertama yang harus ditanam secara utuh dan integral dalam diri manusia, sebab dari konsep tauhid inilah penelitian ini bertujuan untuk (1) Untuk mengetahui pendapat para mufasir terhadap kandungan surah Ash-Shaffat 100-110. (2) Untuk mengetahui nilai-nilai pendidikan di dalam keluarga. (3) Untuk esensi pendidikan tauhid di dalam keluarga yang terkandung dalam surah Ash-Shaffat 100-110. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif bersumber dari kepustakaan (library research). mengingat semua data yang menjadi acuan dalam skripsi ini berasal dari bahan-bahan tertulis, baik dalam bentuk kitab, buku maupun media bacaan lainnya yang representatif serta relevan dengan objek pembahasan. Dari hasil penelitian ini menunjukkan esensi yang terkandung dalam surah Ash-shaffat ayat 100-110. (1) Pendidikan yang terkuat berupa keimanan (2) Patuh kepada orang tua bukti taat kepada Allah (3) Sikap sabar dalam ujian. Nilai-nilai pendidikan dari surah Ash-Shaffat ayat 100-110 (1) keimanan (2) kepatuhan (3) kesabaran.